Pengaruh Bauran Pemasaran Bank Terhadap Loyalitas Nasabah (BTN Syariah KC Surabaya) - Zuhria, Amina Tuz; Anwar, Moch. Khoirul (Jurnal Ekonomika dan Bisnis Islam, 2018)
The purpose of this study is to know how the influence of marketing mix variables of the bank on customer loyalty at BTN Syariah Kc Surabaya. This research is quantitative research. Methods of data collection used questionnaires distributed to respondents. The number of samples (respondents) in this research that is 100 customers selected by purposive sampling technique. Data analysis used a simple regression statistic model. The data were processed using the test of reliability, validity test, classical assumption test and statistical test. From result of data processing show that Marketing Mix of Bank have positive and significant influence to customer loyalty with influence value 13,6% and proven t count (3,395) bigger than (>) t table (1,987), so it can be concluded that the higher Marketing Mix of the Bank, the higher the loyalty of customers at BTN Syariah Kc Surabaya